Assessing the ecological impacts of invasive plants in Neotropical forests through evidence synthesis - Jacob, Igor Nogueira (2023)
Present in all ecosystems in the world, invasive species causes widespread negative ecological impacts on the composition, structure and functioning of their invaded habitats. Simultaneously with the emerging federal legislation and multilateral international agreements that have been put in place to mitigate these impacts, there has also been an exponential growth of publications on invasion ecology in the last decades. The increase of evidence on the ecological impacts of invasive plants over time has been critical not only to elucidate the consequences of different species in specific contexts but also to enable synthesis efforts on the accumulated evidence base. Several reviews in the field of invasion biology have also highlighted the low proportion of research in developing countries in the tropical zone relative to developed countries mainly in the northern hemisphere. Recognizing that evidence reviews are vital tools to inform management, policy and research in conservation and environmental science, the present research aims to systematically collate and analyze the ecological impacts of invasive plants in the Neotropics in two complementary chapters. First, we sought to identify gaps and trends in primary research published in the peer-reviewed literature on the ecological impacts of invasive plants in tropical and sub-tropical forests throughout the Neotropics, following a systematic map approach. Second, we used the dataset from the first chapter of this dissertation to perform a meta-analysis in order to estimate the magnitude and direction of the effects of terrestrial invasive plants on native plant species and communities of tropical and subtropical moist and dry Neotropical forests.